UJI DAYA HAMBAT EKSTRAK Chaetoceros calcitrans TERHADAP BAKTERI Aeromonas salmonicida - Maftuch, Mr.; Setyawan, Febby Hadi; Suprastyani, Heny (JFMR (Journal of Fisheries and Marine Research), 2018)
The impact of use antibiotic can cause problems on aquaculture such as bacterial resistance and residues for consumer. Therefore, one of alternatives that can be used to inhibit or kill bacteria, one of which is the use of plankton Chaetoceros calcitrans. This research aims to know the influence of the granting C. calcitrans extract that can inhibit or kill bacteria and know the best dose for inhibit A. salmonicida bacteria. The experiment methodÂ  used randomize completely design consist of four treatment and two control. A treatment (0.3 ppm), B treatment (15.3 ppm), C treatment (30.3 ppm),Â  D treatment (45.3 ppm), positive control (add chlorampenicol 5ppm) and negative control (without extract). The result of research showed the highest average of clear zone diameter in D treatment 5.37 mm and the lowest average of clear zone diameter in A treatment 2.89 mm, with linear equation y = 3.2067 + 0.0509x and coefficients R2 = 0.9262. The relationship between C. calcitrans extract in inhibitng gwoth of A. salmonicida bacteria showed that the average diameter of the clear zone has increase in line with the addition of extracts. Form the research showed that the extract of C. calcitrans was bacteriostatic (inhibits the growth of bacteria) and best obtained at the treatment dosage of D with a dose of 45.3 ppm and included into the category of middle.